Multifunctional quasi-homogeneous catalyst for lithium oxygen battery and preparation method of multifunctional quasi-homogeneous catalyst
By using multi -functional average catalysts in lithium oxygen batteries, the problem of excessive charging voltage of lithium oxygen batteries and low circulation stability, and realized the broadenness of electrolyte electrochemical windows, the protection of lithium metal negative electrode, and discharge capacity The reduction of the increase and charging potential has significantly improved the cycle stability of the battery.
Patent Information
- Application Number
- CN202411285550.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-24
AI Technical Summary
Lithium-oxygen batteries have problems such as excessive charging voltage, premature battery failure, cycle life and low energy conversion efficiency, which are mainly due to poor conductivity of battery discharge products and easy corrosion of lithium metal negative electrodes.
The multifunctional permanent catalyst is used. The catalyst consists of carbon nanomaterials containing active catalytic sites. By introducing transition metal ions such as RU3+and RU2+, combined with carbon quantum dots and carbonized polymer points to form nano -carbon bases, the size is in the size in the size, the size is on Between 1nm ~ 10nm. The catalyst is prepared through the solvent thermal reaction and precipitation method, and adds a lithium oxygen battery electrolyte.
It significantly broadens the electrolyte electrochemical window, protects the lithium metal anode, increases discharge capacity, reduces charging overpotential, improves cycle stability, and enhances the cycle life and energy conversion efficiency of the battery.
Smart Images

Figure CN119361726A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal-air batteries, and specifically relates to a multifunctional quasi-homogeneous catalyst for lithium-oxygen batteries and a preparation method thereof. Background Art
[0002] At present, the rapid popularization and development of electric vehicles and portable electronic devices have put forward higher requirements for battery life. The traditional battery system can no longer meet the development of energy storage technology and the demand for large-capacity electrochemical energy storage equipment. Therefore, it is necessary to design and develop new energy storage technologies.
[0003] Lithium-oxygen batteries have an ultra-high theoretical energy density of up to 3500Wh / kg. They are one of the new battery technologies that my country is focusing on developing and have very broad application prospects. However, there are some problems with current lithium-oxygen batteries. First, their charging voltage is too high, which will cause the decomposition of the electrolyte and the electrode, leading to premature failure of the battery, thereby limiting the battery's cycle life and energy conversion efficiency. The main reason for this phenomenon is that the battery discharge product has poor conductivity, which makes it difficult to effectively decompose during the cycle, gradually accumulating on the positive electrode side, and causing the battery polarization to gradually increase. In addition, lithium-oxygen batteries also have problems with the easy corrosion of the lithium metal negative electrode and the growth of dendrites, as well as the narrow electrochemical window of the electrolyte and easy decomposition at high potentials.
[0004] The main strategies for reducing the charge overpotential of lithium-oxygen batteries and improving cycle stability include the use of solid-phase catalysts and the introduction of redox mediators into the electrolyte. Solid-phase catalysts promote the decomposition of discharge products through their active catalytic sites, thereby effectively reducing the charge voltage. However, during the battery cycle, the active sites of the solid-phase catalysts are easily covered by byproducts and passivated discharge products and become ineffective. On the other hand, the redox mediator first undergoes an oxidation reaction at the positive electrode and then assists in the oxidation and decomposition of the discharge products. This process significantly reduces the overpotential of the charging process. However, the redox mediator in the oxidized state also has the phenomenon of side reactions with the lithium metal negative electrode, namely the shuttle effect, which impairs the stability of the battery.
[0005] Therefore, new solutions need to be proposed based on the characteristics of lithium-oxygen batteries. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above background and / or problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the core purpose of the present invention is to overcome the deficiencies in the prior art and provide a multifunctional quasi-homogeneous catalyst for lithium-oxygen batteries.
[0009] To achieve the above technical objectives, the present invention adopts the following technical solution: a multifunctional quasi-homogeneous catalyst for lithium-oxygen batteries, wherein the catalyst is a carbon nanomaterial containing active catalytic sites.
[0010] As a preferred embodiment, the catalyst structure includes transition metal ions and a nanocarbon substrate.
[0011] As a preferred embodiment, wherein: the transition metal ion comprises Ru 3+ And Ru 2+ One or more of .
[0012] As a preferred embodiment, the nanocarbon substrate is one or more of carbon quantum dots and carbonized polymer dots.
[0013] As a preferred embodiment, the size of the nano-carbon substrate is 1 nm to 10 nm.
[0014] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for synthesizing a multifunctional quasi-homogeneous catalyst for a lithium-oxygen battery, the specific steps of which are as follows:
[0015] Mixing ruthenium salt, 5-aminophenanthroline and citric acid in a reaction solvent to obtain a homogeneous mixed solution;
[0016] subjecting the mixed solution to a solvothermal reaction to obtain a homogeneous reaction solution;
[0017] The homogeneous reaction solution is added with an excess amount of precipitation solvent and filtered to obtain a quasi-homogeneous catalyst.
[0018] As a preferred embodiment, the ruthenium salt is one or more of hydrated ruthenium chloride and ruthenium acetylacetonate.
[0019] The added amount of ruthenium element is 5wt% to 20wt%.
[0020] As a preferred embodiment, the reaction solvent is one or more of water, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
[0021] As a preferred embodiment, the solvent thermal reaction temperature is 120 to 220° C., and the solvent thermal reaction time is 2 to 12 hours.
[0022] As a preferred embodiment, the precipitation solvent is one or more of ethanol, acetonitrile, acetone, ethyl acetate and ether.
[0023] The present invention also provides an application of the multifunctional quasi-homogeneous catalyst in a lithium-oxygen battery to optimize and compare the catalytic performance of the multifunctional quasi-homogeneous catalyst.
[0024] Specifically, the application is to add the multifunctional quasi-homogeneous catalyst into a lithium-oxygen battery electrolyte to assemble a lithium-oxygen battery.
[0025] As a preferred embodiment, the electrolyte includes a quasi-homogeneous catalyst, a lithium salt, and an organic solvent.
[0026] The addition amount of the quasi-homogeneous catalyst is 0.05wt% to 1wt%.
[0027] The lithium salt includes one or more of lithium trifluoromethanesulfonate, lithium perchlorate, lithium nitrate and lithium bis(trifluoromethanesulfonyl)imide.
[0028] Wherein, the concentration of the lithium salt is 0.5M to 2M.
[0029] Wherein, the organic solvent includes one or more of tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether and dimethyl sulfoxide.
[0030] As a preferred embodiment, the lithium oxygen battery comprises the above-mentioned electrolyte, a negative electrode, a positive electrode and a separator.
[0031] As a preferred solution, the positive electrode includes one or more of a conductive agent, a current collector and a binder.
[0032] Wherein, the conductive agent includes one or more of carbon black, Ketjen black, graphite, carbon nanotubes, amorphous carbon, Super P and nanoporous carbon.
[0033] Wherein, the current collector comprises one or more of stainless steel mesh, nickel foam, conductive carbon cloth and conductive carbon paper.
[0034] Wherein, the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene latex, polyvinyl pyrrolidone and carboxymethyl cellulose.
[0035] As a preferred solution, the diaphragm preferably includes one or more of a glass fiber membrane, a PP membrane, a PE membrane, and a PTFE membrane.
[0036] Beneficial effects of the present invention:
[0037] (1) As a key component of lithium-oxygen batteries, the multifunctional quasi-homogeneous catalyst of the present invention can be evenly dispersed in the electrolyte to broaden the electrochemical window of the electrolyte, effectively protect the lithium metal negative electrode, significantly increase the discharge capacity, and reduce the charging overpotential. Ultimately, the cycle stability of the lithium-oxygen battery is greatly enhanced.
[0038] (2) The multifunctional quasi-homogeneous catalyst of the present invention can combine with electrolyte solvent molecules and significantly broaden the electrochemical window of the electrolyte by reducing the energy of the highest occupied orbital energy level of the solvent molecules; effectively protect the lithium metal negative electrode by finely regulating the solvation structure and electrostatic shielding mechanism; significantly improve the discharge capacity by stabilizing superoxide intermediates; and reduce the charge overpotential and improve the cycle stability by means of the co-deposition mechanism and catalytic active sites.
[0039] (3) The multifunctional quasi-homogeneous catalyst of the present invention is used in lithium-oxygen batteries, which effectively improves the battery cycle stability and provides an important approach to performance optimization of lithium-oxygen batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0041] Table 1 is a table of the final pressure data of the first charge cycle of the lithium oxygen batteries of Examples 1 to 3 of the present invention and Comparative Example 3.
[0042] Table 2 is a full battery performance data table of Example 1 of the present invention and Comparative Examples 1-2.
[0043] Figure 1 The electrochemical window test curves of the electrolytes of Example 1 and Comparative Example 1 of the present invention are shown.
[0044] Figure 2 1 and 2 are the lithium-lithium symmetric battery cycle curves of Example 1 and Comparative Example 1 of the present invention.
[0045] Figure 3 The first deep discharge curves (cut-off voltage: 2 V, discharge current: 200 mA / g) of the lithium oxygen batteries of Example 1 and Comparative Examples 1-2 of the present invention are shown.
[0046] Figure 4 The first cycle charge and discharge curves of the lithium oxygen batteries of Examples 1 to 3 of the present invention and Comparative Example 3 (current: 500 mA / g, capacity: 1000 mAh / g).
[0047] Figure 5 The first cycle charge and discharge curves of the lithium oxygen batteries of Example 1 and Comparative Examples 1-2 of the present invention (current: 500 mA / g, capacity: 1000 mAh / g).
[0048] Figure 6The graphs are the cycle performance test graphs of the lithium oxygen batteries of Example 1 and Comparative Examples 1-2 of the present invention (current: 500 mA / g, capacity: 1000 mAh / g). DETAILED DESCRIPTION
[0049] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0050] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0051] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0052] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available, as shown in Table 1 for details.
[0053] Table 1
[0054] name Commercial channels Part Number 5-Aminophenanthroline Maclean P816909-1g Ruthenium acetylacetonate Maclean R817342-1g Citric Acid Aladdin C108869-100g
[0055] Example 1
[0056] (1) Synthesis of multifunctional quasi-homogeneous catalyst for lithium oxygen battery: 0.195 g of 5-aminophenanthroline, 0.192 g of citric acid and 0.240 g of hydrated ruthenium chloride were stirred and mixed in 15 mL of N,N-dimethylformamide to form a homogeneous mixed solution (the amount of ruthenium added was 15.5 wt%). The homogeneous mixed solution was subjected to solvothermal reaction at 200° C. for 4 h. The obtained reaction solution was added with excess ethyl acetate and filtered to obtain 0.200 g of quasi-homogeneous catalyst.
[0057] (2) Preparation of an electrolyte containing the multifunctional quasi-homogeneous catalyst: In an argon glove box, 0.020 g of the quasi-homogeneous catalyst and 0.574 g of lithium salt lithium bistrifluoromethylsulfonyl imide were stirred and dissolved in 2 mL of ultra-dry tetraethylene glycol dimethyl ether (lithium salt concentration was 1 M). Stirring in the argon glove box for 30 min, an electrolyte containing the multifunctional quasi-homogeneous catalyst was obtained (the content of the multifunctional quasi-homogeneous catalyst was 0.8 wt%).
[0058] (3) An electrochemical window test was performed on the electrolyte containing the multifunctional quasi-homogeneous catalyst prepared in Example 1 of the present invention. The methods and parameters for performing the electrochemical window test in other embodiments and comparative examples were the same as those in this embodiment.
[0059] Electrolyte electrochemical window test process: The electrolyte containing the multifunctional quasi-homogeneous catalyst is used as the test battery electrolyte, and lithium sheets (brand: Zhongneng Lithium; thickness: 200μm, diameter: 14mm), glass fiber membrane (brand: Whatman; diameter: 16mm), electrolyte (addition amount: 60μL), stainless steel sheets (model: 304; diameter: 16mm), stainless steel shrapnel (model: 304; diameter: 16mm) are placed in the middle of the positive and negative shells of the button battery in turn, and finally assembled into a button battery under a certain pressure using a button battery packaging machine, and a linear sweep voltammetry test is performed. The linear sweep voltammetry is tested using the BioLogic VMP3 electrochemical workstation, and the test parameters are: the temperature is room temperature; the scan rate is set to 0.05mV / s; the scan range is 1.0~6.0V.
[0060] The methods and parameters for testing the electrochemical window of the electrolyte in other embodiments and comparative examples are the same as those in this embodiment.
[0061] The electrochemical window comparison curves of the electrolytes of Example 1 and Comparative Example 1 of the present invention are shown in Figure 1 .Depend on Figure 1 It can be seen that the addition of the multifunctional quasi-homogeneous catalyst significantly improved the electrochemical window, and the electrochemical oxidation starting voltage was 5.1V.
[0062] (4) A lithium-lithium symmetric battery cycle test was performed on the electrolyte containing the multifunctional quasi-homogeneous catalyst prepared in Example 1 of the present invention. The methods and parameters for performing the lithium-lithium symmetric battery cycle test in other examples and comparative examples were the same as those in this example.
[0063] The steps for assembling the test battery are the same as those described above, except that the stainless steel sheet is replaced with a lithium sheet (brand: Zhongneng Lithium; thickness: 200 μm, diameter: 14 mm).
[0064] The lithium-lithium symmetrical battery was subjected to a cycle test with the following test parameters: standing for 5 h, current 0.462 mA, discharge for 1 h, and charge for 1 h.
[0065] The comparison of the cycle performance of the lithium-lithium symmetric battery of Example 1 of the present invention and Comparative Example 1 is shown in Figure 2 .Depend on Figure 2 It can be seen that the cycle stability of lithium-lithium symmetric batteries using electrolytes containing multifunctional quasi-homogeneous catalysts has been significantly improved, and the cycle time can reach 300h.
[0066] (5) A discharge test was performed on the lithium oxygen battery prepared in Example 1 of the present invention. The methods and parameters for the discharge test of the lithium oxygen batteries in other embodiments and comparative examples were the same as those in this embodiment.
[0067] This embodiment provides a lithium-oxygen battery, in which the cathode gas (ie, working gas) used is oxygen, the cathode is metallic lithium, and the cathode is composed of carbon nanotubes and carbon paper.
[0068] Among them, carbon nanotubes act as a conductive agent and carbon paper acts as a current collector.
[0069] Among them, the positive electrode can be made by the following method:
[0070] The carbon nanotubes and the polyvinylidene fluoride binder are uniformly dispersed in N-methylpyrrolidone in a weight ratio of 4:1 to obtain a uniformly mixed slurry;
[0071] Add the above slurry dropwise onto the carbon paper;
[0072] The carbon paper coated with the slurry was dried in a vacuum environment at 80°C for 24 h to evaporate the residual solvent. Finally, the overall mass was weighed, and the final loading mass of the carbon nanotubes was 0.1 mg / cm 2 .
[0073] The electrolyte containing the multifunctional quasi-homogeneous catalyst is used as the test battery electrolyte. The lithium sheet (brand: Zhongneng Lithium; thickness: 200μm, diameter: 14mm), glass fiber membrane (brand: Whatman; diameter: 16mm), electrolyte (addition amount: 100μL), and positive electrode sheet (diameter: 12mm) are placed in the middle of the positive and negative shells of the button battery in turn. Finally, a button battery packaging machine is used to assemble the button battery under a certain pressure. The positive electrode shell of the button battery has multiple openings with a diameter of 1mm. The battery is placed in a lithium oxygen battery test container, which is provided with a vent and an outlet. The test container is evacuated and then filled with oxygen.
[0074] The first discharge capacity parameters were tested using Wuhan Blue Electric Battery Tester. The test parameters were: current density of 200 mA / g and cut-off voltage of 2.0 V.
[0075] The first discharge curves of the lithium oxygen batteries of Example 1 and Comparative Examples 1 and 2 of the present invention are shown in Figure 3 , discharge capacity data comparison see Table 2, by Figure 3 As shown in Table 2, the discharge capacity of lithium-oxygen batteries using electrolytes containing multifunctional quasi-homogeneous catalysts has been significantly improved, reaching 7275 mAh / g.
[0076] (6) The first cycle charge and discharge test was performed on the lithium oxygen battery prepared in Example 1 of the present invention. The methods and parameters for the first cycle charge and discharge test of the lithium oxygen battery in other embodiments and comparative examples were the same as those in this embodiment.
[0077] The steps for assembling the test cell are the same as above.
[0078] The first cycle of charge and discharge test was carried out using Wuhan Blue Electric Battery Tester, with test parameters: current density of 500mA / g and limited capacity of 1000mAh / g.
[0079] The first cycle charge and discharge curves of the lithium oxygen batteries of Examples 1 to 3 of the present invention and Comparative Example 3 are shown in Figure 4 , charging final voltage data comparison see Table 1; the first cycle charge and discharge curves of the lithium oxygen battery of Example 1 of the present invention and Comparative Examples 1 and 2 are shown in Figure 5 , charging final voltage data comparison see Table 2, Figure 4 and Figure 5 As shown in Table 1 and Table 2, the charging overpotential of the lithium oxygen battery in Example 1 is significantly reduced, and the charging terminal voltage is 3.75V.
[0080] (7) The battery cycle performance test was performed on the lithium oxygen battery prepared in Example 1 of the present invention. The methods and parameters for the first cycle charge and discharge test of the lithium oxygen battery in other embodiments and comparative examples were the same as those in this embodiment.
[0081] The steps for assembling the test cell are the same as above.
[0082] The battery cycle performance test was carried out using Wuhan Blue Electric Battery Tester, and the test parameters were: current density of 500mA / g and limited capacity of 1000mAh / g.
[0083] The battery cycle performance test results of the lithium oxygen batteries of Example 1 of the present invention and Comparative Examples 1 and 2 are shown in Figure 6 , the battery cycle comparison is shown in Table 2. Figure 6 As shown in Table 2, the cycle stability of lithium-oxygen batteries using electrolytes containing multifunctional quasi-homogeneous catalysts has been significantly improved, and the number of cycles can reach 168.
[0084] Example 2
[0085] The difference from Example 1 is that in step (2), the amount of the quasi-homogeneous catalyst added is replaced with 0.002 g, that is, the content of the multifunctional quasi-homogeneous catalyst is replaced with 0.08 wt %.
[0086] The lithium oxygen battery prepared in Example 2 of the present invention was subjected to a first cycle charge and discharge test.
[0087] The first cycle charge and discharge curves of the lithium oxygen batteries of Examples 1 to 3 of the present invention and Comparative Example 3 are shown in Figure 4 , charging final voltage data comparison see Table 1, Figure 4 From Table 1, it can be seen that the charging terminal voltage of the lithium oxygen battery using the multifunctional quasi-homogeneous catalyst electrolyte prepared in Example 2 is 4.00V.
[0088] Example 3
[0089] The difference from Example 2 is that in step (1), the amount of ruthenium acetylacetonate added is replaced with 0.120 g, that is, the amount of ruthenium added is replaced with 7.7 wt %.
[0090] The lithium oxygen battery prepared in Example 3 of the present invention was subjected to a first cycle charge and discharge test.
[0091] The first cycle charge and discharge curves of the lithium oxygen batteries of Examples 1 to 3 of the present invention and Comparative Example 3 are shown in Figure 4 , charging final voltage data comparison see Table 1, Figure 4 From Table 1, it can be seen that the charging terminal voltage of the lithium oxygen battery using the multifunctional quasi-homogeneous catalyst electrolyte prepared in Example 3 is 4.20V.
[0092] Comparative Example 1
[0093] (1) Preparation of electrolyte for lithium oxygen battery: In an argon glove box, 0.574 g of lithium salt lithium bis(trifluoromethylsulfonyl)imide was stirred and dissolved in 2 mL of ultra-dry tetraethylene glycol dimethyl ether (lithium salt concentration was 1 M). The electrolyte was obtained by stirring in the argon glove box for 30 min.
[0094] (2) An electrochemical window test was performed on the electrolyte prepared in Comparative Example 1 of the present invention.
[0095] The electrochemical window comparison curves of the electrolytes of Example 1 and Comparative Example 1 of the present invention are shown in Figure 1 .Depend on Figure 1 It can be seen that the starting voltage of electrochemical oxidation of the electrolyte without the addition of the multifunctional quasi-homogeneous catalyst is 4.3V.
[0096] (3) A lithium-lithium symmetric battery cycle test was performed on the electrolyte containing the multifunctional quasi-homogeneous catalyst prepared in Comparative Example 1 of the present invention.
[0097] The comparison of the cycle performance of the lithium-lithium symmetric battery of Example 1 of the present invention and Comparative Example 1 is shown in Figure 2 .Depend on Figure 2 It can be seen that the cycle time of the lithium-lithium symmetric battery using the electrolyte without the addition of the multifunctional quasi-homogeneous catalyst is 71h.
[0098] (4) A discharge test was performed on the lithium oxygen battery prepared in Comparative Example 1 of the present invention.
[0099] The first discharge curves of the lithium oxygen batteries of Example 1 and Comparative Examples 1 and 2 of the present invention are shown in Figure 3 , discharge capacity data comparison see Table 2, by Figure 3 From Table 2, it can be seen that the discharge capacity of the lithium-oxygen battery without the addition of the multifunctional quasi-homogeneous catalyst is 5340 mAh / g.
[0100] (5) The lithium oxygen battery prepared in Comparative Example 1 of the present invention was subjected to the first cycle charge and discharge test.
[0101] The first cycle charge and discharge curves of the lithium oxygen battery of Example 1 and Comparative Examples 1 and 2 of the present invention are shown in Figure 5 , charging final voltage data comparison see Table 2, Figure 5 From Table 2, it can be seen that the charging terminal voltage of the lithium-oxygen battery using the electrolyte without adding the multifunctional quasi-homogeneous catalyst is 4.46V.
[0102] (6) The battery cycle performance test was performed on the lithium oxygen battery prepared in Comparative Example 1 of the present invention.
[0103] The battery cycle performance test results of the lithium oxygen batteries of Example 1 of the present invention and Comparative Examples 1 and 2 are shown in Figure 6 , the comparison of the number of cycles is shown in Table 2. Figure 6 From Table 2, it can be seen that the number of cycles of the lithium-oxygen battery using the electrolyte without adding the multifunctional quasi-homogeneous catalyst is 79.
[0104] Comparative Example 2
[0105] (1) Preparation of electrolyte for lithium oxygen battery: In an argon glove box, 0.574 g of lithium salt lithium bis(trifluoromethylsulfonyl)imide was stirred and dissolved in 2 mL of ultra-dry tetraethylene glycol dimethyl ether (lithium salt concentration was 1 M). The electrolyte was obtained by stirring in the argon glove box for 30 min.
[0106] (2) A discharge test was performed on the lithium oxygen battery prepared in Comparative Example 2 of the present invention.
[0107] The lithium oxygen battery assembly and positive electrode preparation methods are the same as those in Example 1, except that the carbon nanotubes are replaced with Ru@CNT as a comparative example using a solid phase catalyst.
[0108] The first discharge curves of the lithium oxygen batteries of Example 1 and Comparative Examples 1 and 2 of the present invention are shown in Figure 3 , discharge capacity data comparison see Table 2, by Figure 3 As shown in Table 2, the discharge capacity of the lithium-oxygen battery without adding the multifunctional quasi-homogeneous catalyst but using the solid-phase catalyst is 5642 mAh / g.
[0109] (3) The lithium oxygen battery prepared in Comparative Example 2 of the present invention was subjected to the first cycle charge and discharge test.
[0110] The first cycle charge and discharge curves of the lithium oxygen battery of Example 1 and Comparative Examples 1 and 2 of the present invention are shown in Figure 5 , charging final voltage data comparison see Table 2, Figure 5 As shown in Table 2, the charging terminal voltage of the lithium-oxygen battery using the electrolyte without adding the multifunctional quasi-homogeneous catalyst but using the solid-phase catalyst is 4.01V.
[0111] (4) The battery cycle performance test was performed on the lithium oxygen battery prepared in Comparative Example 2 of the present invention.
[0112] The battery cycle performance test results of the lithium oxygen batteries of Example 1 of the present invention and Comparative Examples 1 and 2 are shown in Figure 6 , the comparison of the number of cycles is shown in Table 2. Figure 6 As shown in Table 2, the number of cycles of the lithium-oxygen battery using the electrolyte without adding the multifunctional quasi-homogeneous catalyst but using the solid-phase catalyst is 106.
[0113] Comparative Example 3
[0114] The difference from Example 3 is that the ruthenium acetylacetonate in step (1) is replaced by hydrated ruthenium chloride.
[0115] The lithium oxygen battery prepared in Comparative Example 3 of the present invention was subjected to a first cycle charge and discharge test.
[0116] The first cycle charge and discharge curve of the lithium oxygen battery of Comparative Example 3 of the present invention is shown in Figure 4 , charging final voltage data comparison see Table 1, Figure 4 As shown in Table 1, the charging terminal voltage of the lithium oxygen battery using the multifunctional quasi-homogeneous catalyst electrolyte prepared in Comparative Example 3 is 4.32V.
[0117] Table 1
[0118]
[0119] Table 2
[0120]
[0121] Comparative Example 4
[0122] The difference from Example 1 is that 5-aminophenanthroline is not added in step (1). Citric acid and ruthenium acetylacetonate cannot self-assemble to form a polymer structure, and a carbonized polymer dot structure cannot be obtained after a solvothermal reaction, so the catalyst cannot be synthesized.
[0123] Comparative Example 5
[0124] The difference from Example 1 is that citric acid is not added in step (1). 5-Aminophenanthroline forms a complex with ruthenium acetylacetonate, but cannot self-assemble to form a polymer structure, and cannot obtain a carbonized polymer dot structure after solvothermal reaction, so the catalyst cannot be synthesized.
[0125] Comparative Example 6
[0126] The difference from Example 1 is that ruthenium acetylacetonate is not added in step (1). Citric acid and 5-aminophenanthroline cannot self-assemble to form a polymer structure, and a carbonized polymer dot structure cannot be obtained after a solvothermal reaction, so the catalyst cannot be synthesized.
[0127] Comparative Example 7
[0128] The difference from Example 1 is that 5-aminophenanthroline and citric acid are not added in step (1). Ruthenium acetylacetonate itself cannot self-assemble to form a polymer structure, and carbonized polymer dot structures cannot be obtained after solvothermal reaction, so the catalyst cannot be synthesized.
[0129] Comparative Example 8
[0130] The difference from Example 1 is that 5-aminophenanthroline and hydrated ruthenium chloride are not added in step (1). Citric acid itself cannot self-assemble to form a polymer structure, and carbonized polymer dot structures cannot be obtained after solvothermal reaction, so the catalyst cannot be synthesized.
[0131] Comparative Example 9
[0132] The difference from Example 1 is that citric acid and ruthenium acetylacetonate are not added in step (1). 5-Aminophenanthroline itself cannot self-assemble to form a polymer structure, and a carbonized polymer dot structure cannot be obtained after a solvent thermal reaction, so a catalyst cannot be synthesized.
[0133] Comparative Example 10
[0134] The difference from Example 1 is that in step (1), the reaction solvent is replaced by water instead of N,N-dimethylformamide. The raw material has poor solubility in water and cannot form a uniform precursor solution, so the solvothermal reaction cannot be further performed.
[0135] Comparative Example 11
[0136] The difference from Example 1 is that in step (1), the precipitation solvent is replaced by acetone instead of ethyl acetate. When acetone is used, the mass of the catalyst precipitated is less than when ethyl acetate is used, and the yield is smaller.
[0137] The present invention designs a catalyst with both fluidity and catalytic performance, and selects one-dimensional carbon nanomaterial carbonized polymer dots with rich functional groups as the substrate in terms of structure, so that it has good dispersibility in the electrolyte system commonly used in lithium-oxygen batteries. By introducing ruthenium active sites, the catalytic effect of the catalyst on the generation and decomposition process of discharge products is enhanced.
[0138] The quasi-homogeneous catalyst of the present invention has both catalytic performance and fluidity, and can be directly dispersed in the electrolyte of a lithium-oxygen battery as a catalyst. Unlike traditional solid-phase catalysts, it is not loaded and fixed on an electrode for use, but is directly dispersed in the electrolyte and has a certain fluidity. Unlike traditional redox mediators, its catalytic mechanism is mainly through the loaded ruthenium catalytic sites, which is different from the catalytic mechanism of redox mediators and does not have the limitation of the shuttle effect. In addition, the catalyst of the present invention also plays a multifunctional role in lithium-oxygen batteries, including electrolyte regulation and lithium metal negative electrode protection functions.
[0139] The design of the catalyst structure makes the catalyst have both catalytic performance and fluidity; the improvement of the purification method: the product is obtained by using a simple precipitation method instead of a complicated dialysis method; the innovation of the catalyst application method: it is directly added to the electrolyte instead of being loaded on the electrode; the innovation of the catalytic mechanism: the quasi-homogeneous catalyst and the discharge product are co-deposited. Nanomaterials with a size of 1 to 10 nm can be stably and evenly dispersed in the commonly used electrolyte of lithium-oxygen batteries, and have both catalytic performance and fluidity in the generation and decomposition process of the discharge product lithium peroxide, and at the same time have the function of regulating the electrolyte and protecting the lithium metal negative electrode.
[0140] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A multifunctional quasi-homogeneous catalyst for lithium-oxygen batteries, characterized in that: Comprising transition metal ions and nanocarbon substrate; the transition metal ions comprising Ru 3+ And Ru 2+ One or more of the nanocarbon substrate comprises one or more of carbon quantum dots and carbonized polymer dots.
2. The multifunctional quasi-homogeneous catalyst for lithium-oxygen batteries according to claim 1, characterized in that: The catalyst multifunctional quasi-homogeneous catalyst for lithium oxygen battery is a carbon nanomaterial containing active catalytic sites.
3. The multifunctional quasi-homogeneous catalyst for lithium-oxygen batteries according to claim 1, characterized in that: The size of the nano carbon substrate is 1-10 nm.
4. The method for preparing a multifunctional quasi-homogeneous catalyst for lithium-oxygen batteries according to any one of claims 1 to 3, characterized in that: include, Mixing ruthenium salt, 5-aminophenanthroline and citric acid in a reaction solvent to obtain a homogeneous mixed solution; subjecting the mixed solution to a solvothermal reaction to obtain a homogeneous reaction solution; The homogeneous reaction solution is added into a precipitation solvent and filtered to obtain a quasi-homogeneous catalyst.
5. The preparation method according to claim 1, characterized in that: The ruthenium salt includes one or more of hydrated ruthenium chloride and ruthenium acetylacetonate; the amount of ruthenium added in the ruthenium salt is 5wt% to 20wt%.
6. The preparation method according to claim 4, characterized in that: The reaction solvent includes one or more of water, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
7. The preparation method according to claim 4, characterized in that: The solvent thermal reaction temperature is 120-220° C. and the reaction time is 2-12 hours.
8. The preparation method according to claim 4, characterized in that: The precipitation solvent includes one or more of ethanol, acetonitrile, acetone, ethyl acetate and ether.
9. Use of the multifunctional quasi-homogeneous catalyst for lithium-oxygen batteries according to any one of claims 1 to 3 in lithium-oxygen battery electrolyte to assemble lithium-oxygen batteries.
10. The use according to claim 9, characterized in that: The addition amount of the quasi-homogeneous catalyst is 0.05 wt% to 1 wt%.